Diffusion Kurtosis at 3.0T as an in vivo Imaging Marker for Breast Cancer Characterization: Correlation With Prognostic Factors. Issue 3 (8th September 2018) - Huang, Yao; Lin, Yan; Hu, Wei; Ma, Changchun; Lin, Weixun; Wang, Zhening; Liang, Jiahao; Ye, Wei; Zhao, Jiayun; Wu, Renhua
Abstract : Background: Diffusion‐kurtosis imaging (DKI) has preliminarily shown promise as a relatively new MRI technique to provide useful information regarding breast lesions, but the diagnostic performance of DKI has not been fully evaluated. Purpose: To compare the diagnostic accuracy of DKI, diffusion‐weighted imaging (DWI), dynamic contrast‐enhanced (DCE)‐MRI) and proton MR spectroscopy ( 1 H‐MRS) in differentiating malignant from benign breast lesions independently or jointly, and explore the correlation between DKI‐derived parameters and prognostic factors. Study Type: Prospective. Subjects: Seventy‐one patients with breast lesions (50 malignant, 26 benign). Sequence: DKI, DWI, DCE‐MRI, and 1 H‐MRS were performed at 3.0T. Assessment: Mean kurtosis (MK), mean diffusivity (MD), apparent diffusion coefficient (ADC), BI‐RADS category, and choline peaks were analyzed by two experienced radiologists. Statistical Tests: Student's t ‐test was used for continuous variables; receiver operating characteristic (ROC) analysis for assessing the diagnostic accuracy of imaging parameters; Spearman or Pearson correlations for assessing the associations between imaging parameters and prognostic factors. Results: MK exhibited higher area under the curves (AUCs) for differentiating malignant from benign lesions than did MD, ADC, DCE, and tCho (0.979 vs. 0.928, 0.911, 0.777, and 0.833, respectively, P < 0.05). MK showed a positive association with Ki‐67 expression ( r = 0.508) and histologic grades ( r = 0.551), whereas MD and ADC were negatively correlated with Ki‐67 expression ( r = –0.416 and r = –0.458) and histologic grades ( r = –0.411 and r = –0.319). Moreover, MK showed relatively higher AUCs compared with MD and ADC in detecting breast cancers with lymph nodal involvement, histologic grades, and Ki‐67 expression. Data Conclusion: MK has higher diagnostic accuracy compared with ADC, DCE, and tCho regarding detection of breast cancer. Moreover, DKI shows promise as a quantitative imaging technique for characterizing breast lesions, highlighting the potential utility of MK as a promising imaging marker for predicting tumor aggressiveness. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:845–856.